2016
DOI: 10.1007/8904_2016_11
|View full text |Cite
|
Sign up to set email alerts
|

Improved Measurement of Brain Phenylalanine and Tyrosine Related to Neuropsychological Functioning in Phenylketonuria

Abstract: Introduction: Researchers hypothesized that in phenylketonuria (PKU) high brain phenylalanine (Phe) levels and low brain tyrosine (Tyr) levels affect neuropsychological functioning. However, traditional magnetic resonance spectroscopy (MRS) yielded uncertain results of brain Phe and could not adequately measure brain Tyr. This pilot study examined the potential of correlated spectroscopy (COSY) to quantify these biomarkers and explain variability in neuropsychological functioning.Methods: Nine adults with earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
17
0
2
Order By: Relevance
“…We did not measure tyrosine concentrations, or rates of monoamine synthesis directly in nerve terminal in relevant brain tissues in the affected patients. Although a strong correlation has previously been reported between plasma levels of tyrosine and its concentration in cerebrospinal fluid in HT‐1 patients (Thimm et al, ), a recent magnetic resonance spectroscopy study on PKU patients indicated a large concentration gradient between blood and brain (posterior cingulate gyrus and perventricular white matter) levels of phenylalanine and tyrosine (Waisbren et al, ). Still, the effective subcellular concentration of amino acids in relevant compartments of monoaminergic neurons in these patients is not known.…”
Section: Resultsmentioning
confidence: 96%
“…We did not measure tyrosine concentrations, or rates of monoamine synthesis directly in nerve terminal in relevant brain tissues in the affected patients. Although a strong correlation has previously been reported between plasma levels of tyrosine and its concentration in cerebrospinal fluid in HT‐1 patients (Thimm et al, ), a recent magnetic resonance spectroscopy study on PKU patients indicated a large concentration gradient between blood and brain (posterior cingulate gyrus and perventricular white matter) levels of phenylalanine and tyrosine (Waisbren et al, ). Still, the effective subcellular concentration of amino acids in relevant compartments of monoaminergic neurons in these patients is not known.…”
Section: Resultsmentioning
confidence: 96%
“…Recently, two‐dimensional shift correlated spectroscopy has been applied for the unambiguous quantification of cerebral metabolites, Phe and tyrosine, that present spectral overlap via conventional spectroscopy. With this technique, brain concentrations of these metabolites were significantly associated with some indices of neuropsychological functioning (eg, auditory memory and executive functioning) …”
Section: Neuroimagingmentioning
confidence: 99%
“…(14, 15)). Nevertheless, restoration of Phe regulation begins with understanding how unaffected individuals control Phe levels, and why there is extensive variation in phenotype among those who cannot regulate Phe.…”
Section: Phenylketonuria – a Brief Overviewmentioning
confidence: 99%